COMPLEX OF HUMANIST APPROACHES IN THE SYSTEM OF PHYSICAL EDUCATION OF YOUTH - Dmitry Petrenko; Marina Dolzhikova; Alexander Kudrya; Alexander Marchenko; Iveta Tarasenko (Вестник Северо-Кавказского федерального университета, 2022)
The article is devoted to the study of the humanistic approach in school physical education with the aim of turning the school towards a child, respecting his personality, dignity, trust in him, accepting his personal goals, demands and interests, creating the most favorable conditions for revealing his physical abilities and developing his abilities in physical culture and sport, as well as for its successful self-determination in life, the realization of a healthy lifestyle.